The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1111/j.1349-7006.1989.tb01686.x
|View full text |Cite
|
Sign up to set email alerts
|

The × Gene of Hepatitis B Virus Induced Growth Stimulation and Tumorigenic Transformation of Mouse NIH3T3 Cells

Abstract: To examine the transforming potential of the × gene product of hepatitis B virus (HBV), the X‐gene‐containing region (referred to as the HBx region) was introduced into mouse NIH3T3 cells. Each transformed cell line expressed X‐coding mRNA at a different level. A positive correlation was found between the level of X‐coding mRNA and the saturation density of the cells. The HBx‐transformed cell lines exhibited × protein production and tumor formation in nude mice. The function of HBV in oncogenesis may involve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
95
2

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(101 citation statements)
references
References 21 publications
4
95
2
Order By: Relevance
“…However, in a di erent genetic context, HBx transgenic mice show either no obvious pathology (Lee et al, 1990), only increased susceptibility to chemical carcinogens (Slagle et al, 1996), or acceleration of the development of c-mycinduced HCC (Terradillos et al, 1997). Only a few studies have shown transformation of certain cell types by HBx in vitro (Hohne et al, 1990;Shirakata et al, 1989). Thus, the actual impact of HBx in liver carcinogenesis and the mechanisms of its action remain largely obscure.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a di erent genetic context, HBx transgenic mice show either no obvious pathology (Lee et al, 1990), only increased susceptibility to chemical carcinogens (Slagle et al, 1996), or acceleration of the development of c-mycinduced HCC (Terradillos et al, 1997). Only a few studies have shown transformation of certain cell types by HBx in vitro (Hohne et al, 1990;Shirakata et al, 1989). Thus, the actual impact of HBx in liver carcinogenesis and the mechanisms of its action remain largely obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous attempts have been made to examine the oncogenic potential of HBx in cell culture (Hohne et al, 1990;Oguey et al, 1996;Shirakata et al, 1989;Tarn et al, 1999). However, its transforming ability was barely measurable only when cells were immortalized by other oncogenes, such as SV40 T-antigen (Hohne et al, 1990) or TGF-a (Oguey et al, 1996;Tarn et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that HBxAg and WHxAg are also structurally and functionally similar (Galibert et al, 1982), as are both human and woodchuck p53s, further suggests that they may share common properties, possibly including some of the mechanistic steps whereby these viruses mediate hepatocellular transformation. Given the increasing importance of HBxAg to transformation 1994;Shirakata et al, 1989;Hohne et al, 1990;Koike et al, 1994), combined with its complexing to wild type p53 (Feitelson et al, 1993a;Ueda et al, 1995;Truant et al, 1995), it was of great interest to see whether this also occurred in the WHV system. The results of this study show that WHxAg and woodchuck p53 form complexes both in vitro and in vivo in a manner analogous to that which occurs in human carriers with HCC, providing at least part of a common mechanism whereby these viruses cause hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The ®nding that HBxAg is often expressed from viral DNA fragments integrated into human liver or HCC nodules, and that the HBxAg made is still capable of trans-activation (Zahm et al, 1988;Wollersheim et al, 1988), suggest that functional HBxAg is associated with the development of these tumors, although it is not known whether HBxAg associated trans-activation is relevant to hepatocarcinogenesis. In addition, the ®nding that HBxAg transforms NIH3T3 cells (Shirakata et al, 1989) and a nontransformed mouse hepatocyte cell line (Hohne et al, 1990), suggests that under selected conditions, HBxAg can mediate transformation of cultured cells. Further, the ®nding that HBxAg complexes with the tumor suppressor product, p53, in the majority of HBV associated HCC Figure 6 Complex formation between woodchuck p53 and WHxAg in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation